Comparison of Postural Control of novice and expert rhythmic gymnasts Comparación del Control postural de gimnastas rítmicas novatas y expertas - Cares Barrientos, Sergio Oscar; Retamal, Héctor Felipe; Venegas, Rodrigo Guzmán (My University, 2024)
The objective was to determine the differences in the quality of postural control between rhythmic gymnasts with differ-ent experience in performing skills specific to the discipline. The skills evaluated were Assisted Lateral Split (ELCA), Assisted Circle (CCA) and Unaided Back Split (EASA), considered those that generate the greatest muscle activation and changes in the center of pressure (CDP). The study involved 19 rhythmic gymnasts, 9 from the novice group (less than 4 years of experience), and 10 from the expert group (more than 4 years of experience). The execution of the sports skills was carried out on a force platform (model: BP5050. Bertec, USA), where the area and displacement speed of the center of pressure were evaluated. The area of displacement of the center of pressure was greater for all skill in novice gymnasts, compared to the experienced gymnasts, being statistically signifi-cant, in the ELCA skill. The skill that presented the greatest displacement of the center of pressure in novice gymnasts was ELCA, and for experts it was EASA. According to the results, experience influences better postural control, therefore we should start from an early age to focus on work aimed at improving this variable, allowing greater effectiveness and efficiency in this sport, optimizing the development of training and reducing the risk of injuries.
Keywords: experience; postural balance; pressure center; rhythmic gymnastics; sport